2014
DOI: 10.1123/jsep.2013-0070
|View full text |Cite
|
Sign up to set email alerts
|

Testing Measurement Invariance Across Spanish and English Versions of the Physical Self-Description Questionnaire: An Application of Exploratory Structural Equation Modeling

Abstract: Test of measurement invariance across translated versions of questionnaires is a critical prerequisite to comparing scores on the different versions. In this study, we used exploratory structural equation modeling (ESEM) as an alternative approach to evaluate the measurement invariance of the Spanish version of the Physical Self-Description Questionnaire (PSDQ). The two versions were administered to large samples of Australian and Spanish adolescents. First, we compared the CFA and ESEM approaches and showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
1
21
0
4
Order By: Relevance
“…Other studies have compared the physical self-perceptions among adolescents from more diversified cultural background, contrasting those from a more individualistic and collectivistic cultural orientation (Aşçı, Alfermann, Çağlar, & Stiller, 2008;Hagger, Aşçı, & Lindwall, 2004;Hagger, Biddle, Chow, Stambulova, & Kavussanu, 2003;Tomás, Marsh, González-Romá, Valls, & Nagengast, 2014). Aşçı et al (2008) demonstrated that adolescents from Germany (considered as an individualistic culture) tend to have higher levels on many physical self-dimensions (with the exception of appearance, body fat and physical self-worth that were lower) than adolescents from Turkey (considered as a collectivist culture).…”
Section: Latent Means Differences On the Psi-s Factors Across Culturamentioning
confidence: 99%
“…Other studies have compared the physical self-perceptions among adolescents from more diversified cultural background, contrasting those from a more individualistic and collectivistic cultural orientation (Aşçı, Alfermann, Çağlar, & Stiller, 2008;Hagger, Aşçı, & Lindwall, 2004;Hagger, Biddle, Chow, Stambulova, & Kavussanu, 2003;Tomás, Marsh, González-Romá, Valls, & Nagengast, 2014). Aşçı et al (2008) demonstrated that adolescents from Germany (considered as an individualistic culture) tend to have higher levels on many physical self-dimensions (with the exception of appearance, body fat and physical self-worth that were lower) than adolescents from Turkey (considered as a collectivist culture).…”
Section: Latent Means Differences On the Psi-s Factors Across Culturamentioning
confidence: 99%
“…Consequently, the validation of a French version of the PSDQ-S will fill an important gap in providing a reasonably short, yet comprehensive, measure of the physical self-concept for the French-speaking research community. However, the usefulness of such a French version goes well beyond the French community in providing a valuable instrument on which to anchor cross-cultural comparison studies (Tomás, Marsh, González-Romá, Valls, & Nagengast, 2014). In this regard, the availability of a validated French version is particularly important given that French is the official or co-official language in 29 countries and territories worldwide and one of the most commonly used language in North Africa.…”
Section: Adaptations To Other Languagesmentioning
confidence: 99%
“…Além disso, resultados semelhantes foram observados por Jeffcoat (2015), o que levou os pesquisadores a realização de uma segunda fase da pesquisa recorrendo a análise fatorial confirmatória para o teste de melhor ajuste entre as soluções com dois e três fatores, o que culminou na escolha, empiricamente embasada, da solução composta por três fatores. Nesse sentido, pode-se inferir a adequação na utilização do ESEM, uma vez que esse método proporcionou a avaliação dos índices de ajuste dos modelos estimados, não exigindo, por exemplo, a divisão da amostra para a utilização de métodos exploratórios e confirmatórios, o que levaria a perda do poder dos métodos estatístico ao contar com subamostras e, portanto, com menor representatividade da população (Marsh, 2013;Tomás et al, 2014). Do ponto de vista teórico, também faz sentido a manutenção da estrutura com três fatores, haja vista que o conteúdo dos itens que compõe o fator Transcendente diz respeito, não só a capacidade do indivíduo em tomar uma perspectiva de observação centrada, mas também a capacidade de ter consciência verbal dessa perspectiva como um "eu central" imutável que transcende o conteúdo da experiência, com exceção da morte.…”
Section: Discussionunclassified
“…De acordo com Marsh, Morin, Parker e Kaur (2013), esse método agrupa os importantes aspectos da análise fatorial exploratória (AFE) e análise fatorial confirmatória (AFC). Dentre eles, a possibilidade de contar com uma estrutura complexa em que todos os itens podem se correlacionar com todos os fatores, a possibilidade do cálculo de índices de ajustes comumente observados em modelos confirmatórios e avaliação da invariância de modelos fatorais entre grupos (Tomás, Marsh, González-Romá, Valls, & Nagengast, 2014). Dessa forma, o modelo foi testado a partir de índices comumente adotados na literatura: WLSMV χ 2 , df, χ 2 /df, RMSEA, CFI e TLI, tendo como parâmetro os seguintes valores χ 2 / df < 3, RMSEA < 0,06, CFI e TLI > 0,95 (Muthén & Muthén, 2012), essas análises foram realizadas por meio do software Mplus 7.4.…”
Section: Análise De Dadosunclassified